1994
DOI: 10.1128/iai.62.7.2917-2929.1994
|View full text |Cite
|
Sign up to set email alerts
|

Actin accumulation associated with clustered and localized adherence in Escherichia coli isolated from patients with diarrhea

Abstract: Escherfihia coli D2 (serotype 07:H-) that was isolated from a child with diarrhea hybridized with an F1845 DNA probe used to detect diffuse adherence. Strain D2 adhered to tissue culture cells (HeLa and HEp-2 cells) in a clustered pattern but did not autoagglutinate on the cell surface and induced the elongation of microvilli after 3 h of incubation. After 6 h of incubation, the infected cells were positive for fluorescent-actin staining at the site of clustered adherence. When analyzed with a confocal laser s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
5

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 56 publications
(88 reference statements)
2
19
0
5
Order By: Relevance
“…Goluszko et al indicated that the Afa which interacted with DAF could promote bacterial internalization (19). These DAEC strains can induce fingerlike projections extending from the surface of infected tissue culture cells, which embed the bacteria and protect them from gentamicin (2,8,57). It is also likely that bacterial internalization and IL-8 induction depends on the subtype of Afa, since the different adhesins may bind to different sites on DAF molecules and thus cause functional differences (40).…”
Section: Discussionmentioning
confidence: 99%
“…Goluszko et al indicated that the Afa which interacted with DAF could promote bacterial internalization (19). These DAEC strains can induce fingerlike projections extending from the surface of infected tissue culture cells, which embed the bacteria and protect them from gentamicin (2,8,57). It is also likely that bacterial internalization and IL-8 induction depends on the subtype of Afa, since the different adhesins may bind to different sites on DAF molecules and thus cause functional differences (40).…”
Section: Discussionmentioning
confidence: 99%
“…This is a particular drawback for the detection of human AfaE-VIII adhesin-positive ExPEC strains (43)(44)(45). Moreover, the DCA could give overestimated results since several aEPEC strains have been found to be daaC positive (13,(46)(47)(48)(49)(50)(51)(52)(53).…”
Section: Epidemiology Detectionmentioning
confidence: 99%
“…The observation of daaC positivity of some aEPEC strains is indicative that Afa/Dr adhesins are expressed by enterovirulent E. coli strains other than Afa/Dr DAEC (13,(46)(47)(48)(49)(50)(51)(52)(53). Moreover, E. coli isolates displaying daaC and afaBC positivities have been found among AIEC, inflammatory bowel disease (IBD)-associated, and intestinal cancer-associated (6,(138)(139)(140) strains.…”
Section: Diarrheamentioning
confidence: 99%
See 1 more Smart Citation
“…Silica nanoparticles provide a means for rapid diffusion of toxic NO for better biofilm dispersion Hetrick et al (2008Hetrick et al ( , 2009 metal, gallium (Ga), has also been shown to prevent the formation of biofilms that are characteristic of chronic infections (Yamamoto et al, 1994). Ga works by competing out iron (Fe) that is necessary for bacterial metabolism and also serves as a cue for biofilm formation (Banin et al, 2005(Banin et al, , 2006.…”
Section: Biofilmsmentioning
confidence: 99%